Analisis Manajemen Operasional dalam Meningkatkan Efisiensi UMKM: Studi Kasus Usaha Keripik Pisang Khanza Snack - Juli Adevia; Nova Suryani (Program Studi Manajemen dan Magister Manajemen, Fakultas Ekonomika dan Bisnis, Universitas Katolik Widya Mandira, 2025)
This study aims to analyze the influence of operational management practices on operational efficiency in Khanza Snack, a micro business categorized as a Micro, Small, and Medium Enterprise (MSMEs) located in Koto Tangah District, Padang City. The research adopts a descriptive quantitative approach using a case study method, with a single MSME owner serving as the primary respondent. Data were collected through a closed-ended questionnaire using a Likert scale, covering ten operational management variables and one operational efficiency variable. The analysis results indicate that most aspects of operational management fall within the “fairly good” category, with average scores ranging from 3.1 to 3.8. Planning and technology received the highest scores, while distribution and operational finance scored the lowest. These findings suggest that the business has applied basic operational management principles effectively, although improvements are needed, particularly in distribution systems and financial documentation. The study recommends strengthening operational documentation, improving digital literacy, and providing human resource training as strategies to enhance sustainable operational efficiency.